Comparison of a Novel Modality of Erbium-Doped Yttrium Aluminum Garnet Laser-Activated Irrigation and Ultrasonic Irrigation against Mature Enterococcus faecalis Biofilm—An In Vitro Study - Gabrijela Kapetanović Petričević; Antonio Perčinić; Ana Budimir; Anja Sesar; Ivica Anić; Ivona Bago (Bioengineering)
In this in vitro study, we aimed to evaluate and compare the antibacterial efficacy of a novel erbium-doped yttrium aluminum garnet laser modality, shock wave enhanced emission of photoacoustic streaming (SWEEPS), ultrasonically activated irrigation (UAI), and single needle irrigation (SNI) against old bacterial biofilm. A two-week-old Enterococcus faecalis biofilm was cultivated on transversal dentinal discs made from the middle third of the roots of single-rooted, single-canal premolars. Biofilm growth was confirmed using scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). The dentine samples were randomly distributed into three experimental groups and one control group based on the irrigation protocol used: Group 1, SWEEPS; Group 2, UAI; and Group 3, SNI. The root canals were irrigated with a 3% sodium hypochlorite solution. Antibacterial efficacy was evaluated quantitatively through bacterial culture and qualitatively through CLSM and SEM. Both SWEEPS and UAI demonstrated a statistically significant reduction in Enterococcus faecalis colony-forming units (CFUs) (p < 0.001), while SNI did not show a statistically significant reduction (p = 0.553). No significant difference was observed between the efficacy of SWEEPS and UAI (p > 0.05). The SWEEPS and UAI techniques were equally effective in eliminating mature E. faecalis biofilm.